Paciente masculino de 70 años de edad con neumonía bacteriana adquirida en la comunidad. - Ubilla Moran, Gabriela Mikaela (2021)
The focus of this clinical case study in a 75-year-old male patient who presented sudden dyspnea upon admission to the emergency room, minimal fatigue, shortness of breath, a few days old cough, and an oxygen saturation of 90%. In order to provide the corresponding treatment methods, various procedures and techniques are used to follow up and obtain a clear diagnosis, leading to bacterial pneumonia. Bacterial pneumonia is an acute but very serious disease that can inflame the alveoli and fill them with pus. Once diagnosed, they will be treated with intravenous antibiotics such as (amikacin, amoxicillin, ceftriaxone, and clavulanic acid). The basic purpose of this study is to determine the appropriate treatment method according to the clinical situation presented by the patient. It can be concluded that lung diseases such as community-acquired bacterial pneumonia are diseases that affect people of all ages and impair their respiratory function. Bacterial pneumonia can be infected in the external environment or in medical institutions. If there is an underlying chronic disease, it can sometimes become more aggressive.